El componente afectivo en el aprendizaje humano: sentido y significado de la educación para el desarollo de la afectividad - Aznar Minguet, Pilar (Revista Española de Pedagogía, 2018)
Approaching the question from a constructivist point of view, the aim of this article is twofold: firstly using as a basis the theoretical re-examinations of studies centring on the analysis of the relationships between affectivity and cognition, we wish to emphasize, on a theoretical level, thus breaking down the conceptual boundaries which had previously fashioned them as separate «regions» of the mind. And, secondly, we wish to propose, on a practical level, guidelines for educational intervention/action in order to achieve the development of affectivity integrated within the process of personal development
Keywords: componente afectivo; aprendizaje humano; educación; afectividad; Revista Española de Pedagogía